Ibis and the city: bogan kitsch and the avian revisualization of Sydney. (August 2020) - Allatson, Paul; Connor, Andrea
The Australian White Ibis (Ibis) ( Threskiornis molucca ) is one of three endemic Ibis species in Australia. In a short time frame beginning in the 1970s, this species has moved from inland waterways to urban centres along the eastern and southeastern seaboards, Darwin and the Western Australian southwest. Today Ibis are at home in cities across the country, where they thrive on the food waste, water resources and nesting sites supplied by humans. In this article, the authors focus on Sydney to argue that the physical and cultural inroads of Ibis, and the birds' urban homeliness, are resignifying urban surfaces and the multispecies ecologies in which contemporary Australians operate. They explore how the very physical and sensory presence of Ibis disrupts the assumptions of many urban Australians, and visitors from overseas, that cities are human-centric or human-dominant, non-hybrid assemblages. They also introduce to this discussion of disrupted human expectations a cultural parallel, namely, the recent rise of Ibis in popular culture as an icon-in-the-making of the nation and as a totem of the modern Australian city itself. This trend exemplifies an avian-led revisualization of urban spaces, and is notable for its visual appeals to Ibis kitsch, and to working class or 'bogan' sensibilities that assert their place alongside cosmopolitan visions of being Australian. Sometimes kitsch Ibis imagery erupts across the urban landscape, as occurs with many Ibis murals. At other times it infiltrates daily life on clothing, on football club, university and business logos, as tattoos on people's skin, and as words in daily idiom, confirmed by terms such as 'picnic pirates', 'tip turkeys' and 'bin chickens'. The article uses a visual vignette methodology to chart Ibis moves into Sydney and the realms of representation alike, and thus to reveal how new zoöpolitical entanglements are being made in the 21st century.